DAMPAK BULLYING DI SEKOLAH TERHADAP KEPERCAYAAN DIRI SISWA REMAJA - Yuhbaba, Zidni Nuris; Budiman, M. Elyas Arif; Erdah Suswati, Wahyi Sholehah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Bullying at school is still a serious problem for teenagers because it has a big impact on the victim. Bullying causes both physical and psychological problems. The most frequent psychological impact is disruption of self-confidence. The aim of this research was to analyze the relationship between bullying and the level of self-confidence among teenage students at one of the junior high schools in Jember. This research uses a correlational quantitative design with a cross sectional method. The number of samples used was 69 respondents with a total sampling technique. The measuring instruments used for both variables are a bullying questionnaire and a self-confidence questionnaire which have been tested for validity and reliability. Data analysis used the Spearman - Rank test. The results of the research show a p value of 0.000 (p<0.05) so it can be concluded that there is a relationship between bullying and the level of self-confidence in teenagers at SMPN X Jember. Bullying makes a significant contribution to the level of self-confidence in adolescents. Bullying behavior is a factor that can influence a teenager's level of self-confidence. The higher the level of bullying experienced, the lower the level of self-confidence of teenage students. Special attention and handling of bullying cases in schools needs to be increased, both for victims and perpetrators